2014
DOI: 10.1039/c3cp54755h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen- and oxygen-related effects in phthalocyanine crystals: formation of carrier traps and a change in the magnetic state

Abstract: The performance of organic semiconductors as electronic materials is very sensitive to impurity incorporation and reactions. Here we show using first-principles calculations that hydrogen and oxygen impurities introduce distinct changes in the electronic properties of metal phthalocyanines (MPc), a family of organic semiconductors renowned for their light conversion efficiency. Selective adsorption of hydrogen atoms on pyridinic nitrogen atoms of MPc molecules, namely zinc and copper phthalocyanines, modifies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…It is well-known that, because DFT-LDA and DFT-GGA approaches suffer from the so-called band gap problem, higher level methods, such as those View Article Online based on hybrid exchange-correlation functionals, 46,47,63,64 are needed in order to obtain more accurate positions of defect states. However, hybrid functional calculations are not feasible at present for the large P3HT supercells used in this work and will have to be performed in future studies.…”
Section: Impuritymentioning
confidence: 99%
See 2 more Smart Citations
“…It is well-known that, because DFT-LDA and DFT-GGA approaches suffer from the so-called band gap problem, higher level methods, such as those View Article Online based on hybrid exchange-correlation functionals, 46,47,63,64 are needed in order to obtain more accurate positions of defect states. However, hybrid functional calculations are not feasible at present for the large P3HT supercells used in this work and will have to be performed in future studies.…”
Section: Impuritymentioning
confidence: 99%
“…We note that similar physisorbed O 2 configurations have been found in previous DFT studies on several other organic semiconductors, such as C 60 , 61 PCBM, 62 and metal phthalocyanines. 63 As explained in the following, these physisorbed O 2 impurities are typical degradation agents in organic electronics as they create states within the energy band gap of the host system.…”
Section: Oxygen-related Impuritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Besides the utilization of discotics in their bulk, effects of nano-confinement to one-dimensional supramolecular discotic nanowires have been probed 13,14 and various applications in molecular quantum dot technology have been examined. [15][16][17][18] Regarding theoretical work on nanographene materials, an abundance of studies across multiple simulation scales have been carried out in the literature, including ab initio and Density Functional Theory (DFT) analyses for structural and electronic properties [19][20][21][22][23][24][25][26][27][28][29] and charge transfer properties. [30][31][32][33] At the level of molecular wires and bulk molecular crystals, atomistic simulations [34][35][36][37][38][39] have elucidated phenomena of structural, mechanical, thermodynamic and dynamical nature.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several works have recently demonstrated the high affinity of tetrapyrrole molecules to hydrogen, , and the possibility of having an excess of hydrogen atoms bonded to these molecules. , ,, Moreover it has also been demonstrated that the presence of these extra H atoms has an important influence on properties such as the energy band gap, the charge and spin state, or the molecular switching. Two distinct mechanisms involving the formation of N–H bonds have been reported: (1) demetalation of the core prior to the H capture and (2) direct hydrogenation of the aza-N atoms as well as of the central metal atom. , …”
mentioning
confidence: 99%